Prognosis of patients paced for chronic atrioventricular block. Issue 6 (June 1979) - Ginks, W; Leatham, A; Siddons, H
Abstract : Between the years 1960 and 1974, 839 patients were paced for chronic complete atrioventricular block. Analysis of survival compared with the general population showed that 170 deaths were expected according to standard mortality tables and 288 actually occurred, giving a ratio of actual to expected deaths of 1.7:1. Patients with a definite history of myocardial infarction showed a higher than average mortality when paced. Mortality was not influenced whether heart was constant or intermittent, whether the ventricular rate was below or above 40/minutes, or whether QRS duration was greater or less than 0.1 second. Analysis of the age groups paced disclosed the most important correlations. Between the ages of 80 and 89 years paced patients could expect to survive as long as other of the same age without heart block. There was, however, a very high ratio of 4.5:1 for 90 patients in the age group 50 to 59 years. The reason for the high mortality ratio was uncertain but it may have been the result of a greater incidence of underlying coronary artery disease.